Path Analysis Pendapatan Dan Produktivitas Perempuan Pemanen Kopi Arabika Gayo - Ferdiansyah, Yudi; Kuswardani, Retna Astuti; Simanullang, Endang Sari (JURNAL AGRICA, 2025)
Coffee agribusiness has various problems, female workers work for a week in Central Aceh Regency as freelance agricultural workers to help household income. Not all female harvesters work all day, there are female harvesters who work from morning to evening and there are those who only work from morning to afternoon. This research aims to analyze the influence of age, number of dependents, working hours, work experience and plant age through productivity on the income of women arabica gayo coffee harvesters. This research was carried out in Lukup Sabun Tengah Village, Kuta Panang District, Central Aceh Regency, Aceh Province with the number of samples used in this research totaling 45 samples taken by simple random sampling with the analytical tool used was path analysis. The results of this research show that the variables that have a greater direct influence on the income of women who harvest Gayo Arabica coffee are the number of dependents, working hours, work experience and age of the plant, while the variable age has a greater indirect influence through productivity on the income of women who harvest arabica gayo coffee.